PENGALAMAN E-COMMERCE AR: STUDI KASUS MEREK MAYBELLINE DI TOKOPEDIA - Herna, Lia (Universitas Multimedia Nusantara, 2024)
Online shopping culture is one of the popular cultures that is currently developing. This popular culture develops along with the rapid development of new media. E-commerce is starting to utilize Augmented Reality as part of its features. Tokopedia launched an AR feature for consumers to try various makeup products. As AR applications in the consumer market are still emerging, studies on AR are insufficient. In this study, the authors analyzed the level of user acceptance of AR implementation in Tokopedia e-commerce by testing the user experience (UX) dimension using a mixed method. Qualitative methods with 5 respondents and quantitative interviews with a system usability scale (SUS) and a user experience questionnaire (UEQ) were conducted on 23 respondents. The results obtained, SUS got a value of 77.61 and UEQ with the value of each category being greater than the impression value. The AR feature has a very positive reception overall, indicating its potential for future use in all industries. Keywords: augmented reality; user experience; maybelline; tokopedia